Violencia doméstica: modelo de análisis y programas de intervención con agresores. Domestic violence: A model of analysis and intervention programs with batterers - Ortiz, Alejandrina; García, Emilio (Cuadernos de Trabajo Social, 2003)
Domestic violence is present at an alarming rate in today’s societies. It is a complex phenomenon with structural and functional dimensions. It requires a systemic analysis in order to acquire the necessary knowledge to apply the proper treatment. In this work, we present a multidimensional integrative theoretical model to understand and explain domestic violence. It is necessary to know and analyze the profile of the aggressor persons in order to develop, apply and evaluate intervention programs for the batterers o domestic violence situations. We analyze several programs that are available in different countries and we propose an intervention program, which is being developed, directed towards male aggressors in their relationships as partners.